2016
DOI: 10.1016/j.jmgm.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Binding mechanism of CDK5 with roscovitine derivatives based on molecular dynamics simulations and MM/PBSA methods

Abstract: Roscovitine derivatives are potent inhibitors of cyclin-dependent kinase 5 (CDK5), but they exhibit different activities, which has not been understood clearly up to now. On the other hand, the task of drug design is difficult because of the fuzzy binding mechanism. In this context, the methods of molecular docking, molecular dynamics (MD) simulation, and binding free energy analysis are applied to investigate and reveal the detailed binding mechanism of four roscovitine derivatives with CDK5. The electrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…MMPBSA was widely applied in the development of anticancer compounds where kinases were identified as the most promising targets. Recent inhibitor design includes the epidermal growth factor receptor kinase domain (Li et al, 2015 ; Moonrin et al, 2015 ; Zhao et al, 2017 ), anaplastic lymphoma kinase (Kong et al, 2015 ), cyclin-dependent kinases (Li X. L. et al, 2014 ; Czelen, 2016 ; Dong et al, 2016a , b , 2017 ; Arba et al, 2017 ), extracellular signal-regulated kinase 2 (Chen, 2017 ), casein kinase 2 (Wang X. W. et al, 2014 ), sphingosine kinases (Fang et al, 2016 ), Src/Abl tyrosine kinases (Fong, 2015 ; Ma et al, 2015 ), RET tyrosine kinase (Gao et al, 2015 ), PRK1 (Slynko et al, 2014 ), Akt kinase (Lu et al, 2015 ), phosphatidylinositol 3 kinase (Bian et al, 2014 ), and Myt1 kinase (Wichapong et al, 2014 ). As an illustration of the method's performance, Slynko et al observed a correlation coefficient of 0.78 between the experimental pIC 50 of 26 PRK1 inhibitors and computational MMPBSA binding affinities.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%
“…MMPBSA was widely applied in the development of anticancer compounds where kinases were identified as the most promising targets. Recent inhibitor design includes the epidermal growth factor receptor kinase domain (Li et al, 2015 ; Moonrin et al, 2015 ; Zhao et al, 2017 ), anaplastic lymphoma kinase (Kong et al, 2015 ), cyclin-dependent kinases (Li X. L. et al, 2014 ; Czelen, 2016 ; Dong et al, 2016a , b , 2017 ; Arba et al, 2017 ), extracellular signal-regulated kinase 2 (Chen, 2017 ), casein kinase 2 (Wang X. W. et al, 2014 ), sphingosine kinases (Fang et al, 2016 ), Src/Abl tyrosine kinases (Fong, 2015 ; Ma et al, 2015 ), RET tyrosine kinase (Gao et al, 2015 ), PRK1 (Slynko et al, 2014 ), Akt kinase (Lu et al, 2015 ), phosphatidylinositol 3 kinase (Bian et al, 2014 ), and Myt1 kinase (Wichapong et al, 2014 ). As an illustration of the method's performance, Slynko et al observed a correlation coefficient of 0.78 between the experimental pIC 50 of 26 PRK1 inhibitors and computational MMPBSA binding affinities.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%
“…Importantly, several studies including X-ray and molecular modeling have indicated the pivotal role of cysteine (Cys83) in ligands binding to CDK5 in the ATP binding pocket [ 139 , 140 ]. This amino acid may be S-nitrosylated and, fascinatingly, the perturbation of such a process leads to the enhancement of dendrite development in cultured hippocampal neurons, which, of course, influences overall neuronal development [ 120 ].…”
Section: 5-ht 6 R/cdk5 As Possible Dual Target App...mentioning
confidence: 99%